Diplomasi Publik Jepang Melalui Cool Japan dalam Mempromosikan National identity Jepang di Indonesia melalui Anime dan Manga - Annisa Justicia Nabilah (2020)
Starting on August 18, 1977, Japan began to focus its diplomatic direction on Southeast Asian countries into public diplomacy, with a meeting of the Japan and ASEAN (Association of South East Asian Nations) in Manila. Takeo Fukuda, the then Prime Minister of Japan, declared that Japan would no longer be a country using military force. The speech was known as "Fukuda Doctrine". The Fukuda doctrine emphasized that Japan would focus on diplomacy based on "Heart To Heart Relations". One tangible result of the doctrine is that Japan is the main donor in ODA (Official Development Assistance) for ASEAN countries. In 2004, Japan began implementing public diplomacy based on national culture through the Cool Japan policy. Cool Japan is a public diplomacy policy that focuses on the export of Japanese culture, not only Japanese traditional culture, but also Japanese pop culture. In the Japan Diplomatic Bluebook 2004, it was recognized that anime and manga are Japanese pop culture, which are included in the contemporary culture category. Japan uses anime and manga to portray Japanese mythology and culture visually aimed at introducing and explaining to readers and viewers (Indonesian people) how mythology and culture are applied, and meaningful to Japan. Japan practices Cool Japan as a form of public diplomacy, to promote the coolness of Japan. The results of this anime and manga diplomacy include Japanese cultural events, like Jak-Japan Matsuri and Little Tokyo Ennichisai, festivals are the most important in the success of Japanese anime and manga diplomacy, because through this events, there are many elements of Japanese culture as described through anime and manga.